2014
DOI: 10.1007/s10802-014-9887-4
|View full text |Cite
|
Sign up to set email alerts
|

Child ADHD and ODD Behavior Interacts with Parent ADHD Symptoms to Worsen Parenting and Interparental Communication

Abstract: Attention-deficit hyperactivity disorder (ADHD) in children and adults increases risk of parenting difficulties and interparental discord. However, little is known about whether disruptive child behavior and adult ADHD operate additively or synergistically to predict parenting and interparental relationship quality. As part of a larger study, 90 parent couples were randomly assigned to interact with a 9-12 year-old confederate child exhibiting either ADHD/ODD-like behavior or typical behavior. Before these int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 43 publications
2
27
0
Order By: Relevance
“…Finally, Wymbs, Wymbs and Dawson [26] examined the effects of self-reported ADHD symptoms of parents, whose children partly suffered from ADHD, on the interaction with confederate children displaying either ADHD/ODD-like or typical behavior. The authors demonstrated that parental ADHD symptoms were only uniquely correlated with observer-coded negative parenting when confederate child behavior was controlled for.…”
Section: The Influence Of Parental Inattention Hyperactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Wymbs, Wymbs and Dawson [26] examined the effects of self-reported ADHD symptoms of parents, whose children partly suffered from ADHD, on the interaction with confederate children displaying either ADHD/ODD-like or typical behavior. The authors demonstrated that parental ADHD symptoms were only uniquely correlated with observer-coded negative parenting when confederate child behavior was controlled for.…”
Section: The Influence Of Parental Inattention Hyperactivitymentioning
confidence: 99%
“…Dawson summarize the detrimental effect of parental inattention by stating that inattentive parents tend to ignore contextual factors and that they have more difficulties with predicting (and preventing) undesirable child behavior [26].…”
Section: Integration Into Previous Researchmentioning
confidence: 99%
“…Maternal depression, lower household income, and a less-stimulating and supportive home environment have been associated with increased risk of ADHD (Sagiv, Epstein, Bellinger, & Korrick, 2013), and may act as unique environmental influences if they affect children within the same family differently. A more negative parenting approach, with more frequent commands and less frequent praise, has been observed in parents of children with ADHD; however, the direction of this effect is unclear, as this improved when the children took stimulant medication (Danforth, Anderson, Barkley, & Stokes, 1991), and childrens’ ADHD symptoms may interact with parents’ own ADHD symptoms to produce poorer parenting behaviour (Wymbs, Wymbs, & Dawson, 2015). …”
Section: Attention-deficit/hyperactivity Disorder (Adhd)mentioning
confidence: 99%
“…In a study, 430 ADHD parents and 237 normal parents, both having ADHD children were compared and higher parenting stress was found in the ADHD group [6]. Another study was conducted in 2014 on 90 couples with ADHD children [7]. It was observed that more severity of ADHD symptoms in the parents, higher the levels of negative parenting.…”
Section: Discussionmentioning
confidence: 99%